EXPERIENCES OF THE COMBAT USE OF ARTILLERY RECONNAISSANCE FORCES AND TOOLS IN THE CONDUCT OF AIR-ARTILLERY RECONNAISSANCE IN MODERN MILITARY CONFLICTS - Muxammadiyev Donyor Nuriddinovich; Maxsudov Odiljon Arifjonovich (American Journals, 2023)
This article discusses the experience of combating artillery intelligence forces and tools in conducting aero-artillery intelligence in modern western conflicts, artillery is one of the three oldest military units in the land, the main strike force of the modern Armed Forces, and its place in combat time.
Keywords: Artillery, aero-artillery, forces, conflicts, technologies, communications.